Blind frequency offset estimator for OFDM systems - Sakina Atoui; Noureddine Doghmane; Saddek Afifi (Universitas Ahmad Dahlan, 2019)
Orthogonal Frequency Division Multiplexing (OFDM) is of great interest for the development of the fifth-generation technology. It is the cornerstone of Multiple-input multiple-output (MIMO) systems. Even though inter carrier interference (ICI) and inter symbol interference (ISI) have been processed for the fourth-generation standards, they still present a huge problem for the fifth-generation standards. This paper explores the tradeoff between the length of the cyclic prefix and the performances of the OFDM system. It also studies the effect of carrier frequency offset (CFO) on OFDM systems. A blind frequency offset estimator that uses the correlations between the remodulated sequence in the receiver side and the conventional received symbol is presented and a closed form solution is derived. The proposed estimator is derived under short interval when the correlation is high, so it has low computational complexity. Lin and Beek’s estimators are used for comparison. Simulations demonstrate the effectiveness of the proposed estimator under Rayleigh fading channel.